THE RELATIONSHIP OF MBTI AND STUDENT GPA SCORE IN BINUS MANAGEMENT CLASS 2015 - Son Wandrial (Bina Nusantara University, 2016)
This article identified the personality type of students by using MBTI models. There are 16 personality types in the MBTI. The method applied was the MBTI approach where the type and composition of the questionsrelated to the MBTI were taken from the Daft’s book. Questionnaires were distributed through discussion forum Binusmaya to all students in three classes that the writer taught. The questionnaires were distributed throughdiscussion forums, and there were about 158 students, but only 143 students who returned it. There were 41 male students and 102 female students. The result shows that the majority of students have approximately 51,04% introvert type and 58,04 % of students have the sensing type. The students with GPA more than 3,5 are ISFJ type.